ORGANOLEPTIC QUALITY CHARACTERISTICS OF BIANG FISH CRACKERS (Setipinna sp) USING DIFFERENT BINDER - Al Habib Septindri; Syahrul Syahrul; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract This study aims to determine the characteristics of the organoleptic quality of biang fish (Setipinna sp) crackers with a different binder (sago and tapioca). An organoleptic assessment was carried out using a hedonic quality test with a treatment scale of 3 - 9, with 25 panelists being somewhat trained. The method used is experimental, namely conducting experiments on the processing of biang fish crackers with different binders. The design used was a non-factorial Completely Randomized Design (CRD) with 4 treatment levels: wheat flour 500 gr (control / F1); tapioca 400 gr + wheat flour 100 gr (F2), sago 400 gr+ wheat flour 100 gr (F3), and a combination of sago 200 gr, tapioca 200 gr, and wheat flour 100 gr (F4). The results of the organoleptic analysis showed that the F1 treatment was the best treatment with a white appearance (8.48), a distinctive aroma of biang fish meat (7.56), no fish taste with a little flour (7.88), and a crunchy texture (7.73). Keywords: Biang fish, crackers, organoleptic